Thermo-Fluidic Modelling of a Heat Exchanger Tube with Conical Shaped Insert having Protrusion and Dimple Roughness - Singh, Bhanu Pratap; Bisht, Vijay Singh; Bhandari, Prabhakar; Rawat, K.S (Pandawan, 2021)
In the present work, thermo-fluidic behavior of a heat exchanger tube with conical shaped insert has been investigated with the help of finite volume method. To enhance the heat transfer rate, two different types of roughness has been used in conical insert i.e. protrusion and dimple roughness. A three-dimensional computational model with RNG turbulence model is used for the simulation and it has been performed for three different diameters (3 mm, 6 mm and 9 mm) and two different pitch space (120 mm and 180 mm) for both protrusion and dimple roughness. The present model has been validated with Dittus-Boelter equation and with Blasius equation for Nusselt number and friction factor, respectively. For a constant heat flux of 1200 W/m2, effect of roughness, diameter and pitch on Nusselt number and friction factor has been predicted for Reynold number range of 5000 to 30000. From the result, it is found that, the protrusion shaped roughness has better thermal performance factor than dimple shape and diameter of 6 mm has performed better than 3 mm and 9 mm for both the cases of roughness due to favorable flow dynamics.